2020
DOI: 10.1002/nop2.455
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of living with the burden from heart failure treatment: Exploring the patient capacity for self‐care

Abstract: Aim To explore how patients with heart failure perceive their capacity to manage treatment and self‐care. Design A qualitative descriptive study. Methods Patients (N = 17) were recruited from a nurse‐led heart failure outpatient clinic from May–August 2017. Data were collected through individual semi‐structured interviews and analysed using systematic text condensation. Results Three main themes were identified as follows: “Personal characteristics,” “Coping strategies” and “Emotional and informative support.”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…An important finding from the current study for healthcare professionals to heed is that when using self-care tools for home monitoring, our HF patients emphasized that they do not want to read about or be reminded about HF. This may be a way of coping in everyday life when living with HF [53], but it also highlights for healthcare professionals the need to listen to the concerns of their HF patients and individualize their care in person or remotely.…”
Section: Discussionmentioning
confidence: 99%
“…An important finding from the current study for healthcare professionals to heed is that when using self-care tools for home monitoring, our HF patients emphasized that they do not want to read about or be reminded about HF. This may be a way of coping in everyday life when living with HF [53], but it also highlights for healthcare professionals the need to listen to the concerns of their HF patients and individualize their care in person or remotely.…”
Section: Discussionmentioning
confidence: 99%
“…argued that self-care counseling aimed at improving immigrants’ well-being must consider their diverse circumstances [ 17 ]. Patients’ personal characteristics and coping strategies, as well as the emotional and informational support they received from nurses and relatives, affect their self-care strategies [ 18 , 19 ]. A meta-synthesis of 19 qualitative studies on HF patients found that it was essential to consider patients’ individual perceptions of HF to successfully facilitate their development of self-management strategies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In CHF patients in Norway, Nordfonn et al 35 observed moderate correlations between HRQoL scores (MLHFQ total score) and the BoT dimensions (role/social activity limitations and physical/mental fatigue), which are comparable with our findings. In our work, we examined this further by looking at the MLHFQ sub-score, which showed a strong association between emotional sub-score of MLHFQ and the impact of self-care (PETS impact index), further adding to Nordfonn et al 14 conclusions that psychological distress adds to BoT and impairs HRQoL.…”
Section: Discussionmentioning
confidence: 95%
“…BoT specific to CHF has been linked to multiple medications and disjointed healthcare services 12,13 . Emotional burden and an individual's capacity have been highlighted as factors that increase BoT in CHF 14 . Physical symptoms are thought to contribute to emotional burden 15 .…”
Section: Introductionmentioning
confidence: 99%